The Welfare Effects of Private Sector Participation in Guinea's Urban Water Supply - Clarke, George (The World Bank, 1999)
June 2000 - Private sector participation in Guinea's urban water sector has benefited consumers, the government, and, to a lesser extent, the new foreign owners. Performance will improve further when the government starts paying its own water bill on time and when the legislature authorizes the collection of unpaid bills from private consumers. In 1989 the government of Guinea enacted far-reaching reform of its water sector, which had been dominated by a poorly run public agency. The government signed a lease contract for operations and maintenance with a private operator, making a separate public enterprise responsible for ownership of assets and investment. Although based on a successful model that had operated in Côte d'Ivoire for nearly 30 years, the reform had many highly innovative features. It is being transplanted to several other developing countries, so Clarke, Ménard, and Zuluaga evaluate its successes and failures in the early years of reform. They present standard performance measures and results from a cost-benefit analysis to assess reform's net effect on various stakeholders in the sector. They conclude that, compared with what might have been expected under continued public ownership, reform benefited consumers, the government, and, to a lesser extent, the foreign owners or the private operator. Most sector performance indicators improved, but some problems remain. The three most troublesome areas are water that is unaccounted for (there are many illegal connections and the quality of infrastructure is poor), poor collection rates, and high prices. The weak institutional environment makes it difficult to improve collection rates, but the government could take some steps to correct the problem. To begin with, it could pay its own bills on time. Also, the legislature could authorize the collection of unpaid bills from private individuals.